The Routledge companion to feminism and postfeminism - Gamble, Sarah, 1962- (London : Routledge, 2001)
The dictionary entries, covering the major individuals and issues, are essential background to an understanding both of feminism's roots and of the trends that are shaping its future, while a series of essays provides further context.
Originally published as: "The Icon dictionary of feminism and postfeminism", Cambridge: Icon, 1998;and as "The Routledge critical dictionary of feminism and postfeminism", Florence, Ky.: Routledge, 1999.
Includes index.
Bibliography: p.179-181.
The dictionary entries, covering the major individuals and issues, are essential background to an understanding both of feminism's roots and of the trends that are shaping its future, while a series of essays provides further context.
Originally published as: "The Icon dictionary of feminism and postfeminism", Cambridge: Icon, 1998;and as "The Routledge critical dictionary of feminism and postfeminism", Florence, Ky.: Routledge, 1999.
Keywords: Feminism; Feminism -- History; Feminism -- Dictionaries